Pelatihan Digital Marketing Produk Lokal Pada UMKM di Desa Dukuh Damu Kab. Tegal - Sonhaji; Haries Anom SAN; Toto Sudibyo; Sri Lestari; Rizki Fitriani; Amelia Dwi Cahyani (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The development of industry 4.0 and digital transformation are currently the main keys to the movement of micro, small and medium enterprises (MSMEs) in Indonesia. However, they still face three complex problems, namely the lack of digital literacy for marketing, the need for business capital and difficulties in logistics distribution. Market opportunities in the digital era seem increasingly open and will produce many benefits that will be obtained if only MSMEs are smart in transforming to take advantage of digitalization trends.Digital marketing not only helps MSMEs increase sales, but also helps them build brands, increase visibility, and build better relationships with customers. In addition to having a good understanding of digital marketing, MSMEs can also optimize the use of social media. The materials presented to partners: Providing materials through an introduction to the basics of digital marketing, Ethics and Cyber ​​Security Training for MSMEs on Optimizing Social Media by creating social media accounts. Holding effective message training. This ability must be possessed by business actors because with attractive images and messages it will increase the interest of potential consumers to buy the product. The method used is by lectures and by conducting structured practice with a target of achieving at least 75% of Skills and 25% of Knowledge fulfilled